Understanding the development of the respiratory glands. Issue 4 (3rd February 2015) - May, Alison; Tucker, Abigail
Abstract : Background : The submucosal glands (SMGs) of the respiratory system are specialized structures essential for maintaining airway homeostasis. The significance of SMGs is highlighted by their involvement in respiratory diseases such as cystic fibrosis, asthma and chronic bronchitis, where their phenotype and function are severely altered. Uncovering the normal development of the airway SMGs is essential to elucidate their role in these disorders, however, very little is known about the cellular mechanisms and intracellular signals involved in their morphogenesis.Results : This review describes in detail the embryonic developmental journey of the nasal SMGs and the postnatal development of the tracheal SMGs in the mouse. Current knowledge of the genes and signalling molecules involved in SMG organogenesis is also explored.Conclusion : Here we review the temporal localisation and development of the murine respiratory glands in the hope of stimulating further research into the mechanisms required for successful SMG patterning and function. Developmental Dynamics 244:525–539, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: In detail descriptions of nasal and tracheal respiratory gland development are highlighted in this review study in an aim to entice further research.